What contributes to action plan enactment? Examining characteristics of physical activity plans. Issue 4 (18th August 2017) - Fleig, Lena; Gardner, Benjamin; Keller, Jan; Lippke, Sonia; Pomp, Sarah; Wiedemann, Amelie U.
Abstract : Objectives: Individuals with chronic conditions can benefit from formulating action plans to engage in regular physical activity. However, the content and the successful translation of plans into action, so‐called plan enactment, are rarely adequately evaluated. The aim of this study was to describe the content of user‐specified plans and to examine whether participants were more likely to enact their plans if these plans were highly specific, viable, and instrumental. Design and methods: The study presents secondary analyses from a larger behavioural intervention in cardiac and orthopaedic rehabilitation. The content of 619 action plans from 229 participants was evaluated by two independent raters (i.e., qualitative analyses and ratings of specificity) and by participants themselves (i.e., instrumentality and viability). Plan enactment was also measured via self‐reports. Multilevel analyses examined the relationship between these plan characteristics and subsequent plan enactment, and between plan enactment and aggregated physical activity. Results: Participants preferred to plan leisure‐time physical activities anchored around time‐based cues. Specificity of occasion cues (i.e., when to act) and highly instrumental plans were positively associated with plan enactment. Interestingly, individuals who planned less specific behavioural responses (i.e., what to do) were more likely to enact their plans. Plan enactment was positively associated with aggregated behaviour. Conclusions: Interventions should not only emphasize the importance of planning, but also the benefits of formulating specific contextual cues. Planning of the behavioural response seems to require less precision. Allowing for some flexibility in executing the anticipated target behaviour seems to aid successful plan enactment. Statement of Contribution What is already known on this subject? Action planning interventions are efficacious in promoting health behaviour. Characteristics of plan content (i.e., specificity) matter for unconditional behaviour change. Plan enactment (i.e., degree to which plan is followed through) is positively linked to behaviour change. What does this study add? Specificity of occasion cues (i.e., when to act) and highly instrumental plans were positively associated with plan enactment. Individuals who planned less specific behavioural responses (i.e., what to do) were more likely to enact their plans. Planning interventions should focus on specificity of context cues but flexibility of behavioural action.